P‐107: A New Circular Optical‐clear Structure for Full‐screen LCD. Issue 1 (29th May 2019) - Wang, Hailiang; Yang, Yan; Zheng, Binyi; Wu, Ling; Shen, Poping; Li, Junyi
Abstract : We reported a new circular optical‐clear structure for full‐screen LCD. The front camera will be placed under the structure. The structure has outstanding features to meet the camera's needs, such as the superior ability to restore the brightness and color of the environment, lower degree image ghosting and image distortion.